Incidence and risk factors of non–device-associated urinary tract infections in an acute-care hospital. (2nd September 2019) - Strassle, Paula D.; Sickbert-Bennett, Emily E.; Klompas, Michael; Lund, Jennifer L.; Stewart, Paul W.; Marx, Ashley H.; DiBiase, Lauren M.; Weber, David J.
Abstract: Objective: To update current estimates of non–device-associated urinary tract infection (ND-UTI) rates and their frequency relative to catheter-associated UTIs (CA-UTIs) and to identify risk factors for ND-UTIs. Design: Cohort study. Setting: Academic teaching hospital. Patients: All adult hospitalizations between 2013 and 2017 were included. UTIs (device and non-device associated) were captured through comprehensive, hospital-wide active surveillance using Centers for Disease Control and Prevention case definitions and methodology. Results: From 2013 to 2017 there were 163, 386 hospitalizations (97, 485 unique patients) and 1, 273 UTIs (715 ND-UTIs and 558 CA-UTIs). The rate of ND-UTIs remained stable, decreasing slightly from 6.14 to 5.57 ND-UTIs per 10, 000 hospitalization days during the study period ( P = .15). However, the proportion of UTIs that were non–device related increased from 52% to 72% ( P < .0001). Female sex (hazard ratio [HR], 1.94; 95% confidence interval [CI], 1.50–2.50) and increasing age were associated with increased ND-UTI risk. Additionally, the following conditions were associated with increased risk: peptic ulcer disease (HR, 2.25; 95% CI, 1.04–4.86), immunosuppression (HR, 1.48; 95% CI, 1.15–1.91), trauma admissions (HR, 1.36; 95% CI, 1.02–1.81), total parenteral nutrition (HR, 1.99; 95% CI, 1.35–2.94) and opioid use (HR, 1.62; 95% CI, 1.10–2.32). Urinary retention (HR, 1.41; 95% CI, 0.96–2.07), suprapubic catheterization (HR, 2.28; 95% CI, 0.88–5.91), and nephrostomy tubes (HR, 2.02; 95% CI, 0.83–4.93) may also increase risk, but estimates were imprecise. Conclusion: Greater than 70% of UTIs are now non–device associated. Current targeted surveillance practices should be reconsidered in light of this changing landscape. We identified several modifiable risk factors for ND-UTIs, and future research should explore the impact of prevention strategies that target these factors.